1988
DOI: 10.1111/j.1445-2197.1988.tb07573.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenesis of Ureteral Anomalies: A Unifying Theory

Abstract: Extensive gross, microscopic and clinical studies of various ureteral anomalies have enabled investigators to set forth theories regarding the aetiologies of these anomalies consistent with observed fact. Synthesis of these observations allows for a simplified classification of mega‐ureter (primary obstructed. reflux and non‐obstructed, non‐reflux mega‐ureters), ureterocele, duplex ureters and ectopic ureters based upon some combination of mesenchymal differentiation anomalies and location anomalies. A defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Analysis of human and animal specimens has led to the suggestion that the trigone is structurally distinct from the bladder and urethra, differentiating from the common nephric duct and ureter (Hutch, 1972;Tanagho, 1981;Weiss, 1988;Wesson, 1925). Other studies suggest that the bladder muscle (detrusor) might also be part of the trigone structure (Meyer, 1946).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of human and animal specimens has led to the suggestion that the trigone is structurally distinct from the bladder and urethra, differentiating from the common nephric duct and ureter (Hutch, 1972;Tanagho, 1981;Weiss, 1988;Wesson, 1925). Other studies suggest that the bladder muscle (detrusor) might also be part of the trigone structure (Meyer, 1946).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of this membrane may be an intrinsic epithelial defect which causes a so-called stenotic ureterocele. Others have suggested a mesenchymal defect as the primary defect in ureteroceles [Weiss, 1988] because abnormal differentiation of muscle fibers had been observed with various techniques [Tanagho et al, 1965;Tokunaka et al, 1981]. Again, others have stressed pathologic innervation as the prime pathogenetic factor [Friedrich et al, 1987].…”
Section: Discussionmentioning
confidence: 96%
“…Weiss [4] proposed that development of all primary ureteral abnormalities may be accounted for by a basic defect in the interaction between the surrounding mesoblastic cells and the transitional epithelium which lines the bladder, ureter, and collecting ducts. Inappropriate inductive interactions resulting in an increased ratio of fibroblasts to myoblasts might alter the compliance of the ureter, resulting in partial to essentially complete obstructions and reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have suggested a common embryological origin for upper and lower ureteral abnormalities (UPJO, VUR and duplicated systems). Atwell et al [3] and Weiss [4] have proposed a mechanism involving inductive interactions between the transitional epithelium which lines the bladder, ureter, and collecting ducts and the surrounding mesoblastic cells which develop into either myoblasts or fibroblasts. If all abnormalities manifested in a pedigree have such a common embryological origin, the particular urinary tract abnormality which presents in each affected individual may depend on the specific time in development during which the mutation was expressed.…”
Section: Introductionmentioning
confidence: 98%